(untitled) (Journal of Informatics Education and Research, 2025)
The employment process is now much more efficient and effective thanks to artificial intelligence (AI), which has completely transformed talent acquisition and recruitment. AI-powered solutions expedite candidate sourcing by searching enormous databases for prospective employees who meet particular job requirements. Through automated resume parsing, these systems also improve candidate screening, allowing recruiters to concentrate on the most qualified candidates. Furthermore, AI promotes diversity and inclusivity inside organizations by reducing human biases in the screening process, which enables unbiased hiring. The applicant experience is enhanced by chatbots and virtual assistants, which give candidates prompt answers and updates. Another application of AI is predictive analytics, which uses past data to forecast candidate success and retention. Identification of passive candidates—those who match the required profile but may not be actively seeking new opportunities—is another use for AI. Moreover, AI-powered tools can handle monotonous jobs like interview scheduling, freeing up recruiters to focus on making strategic decisions. A sample of 287 is collected from professionals in the HR department. The factors that identify the Role of Artificial Intelligence in Recruitment and Talent Acquisition are Resume Screening and Matching, Chatbots for Initial Interaction, Bias Reduction, and Enhanced Candidate Experience.